Scheduling fertigation for quality Nagpur mandarin - Shirgure, P S; Srivastava, A K (Indian Horticulture, 2019)
Low water- and fertilizer-use efficiency (WUE) and (FUE), respectively, are among major production related constraints. Flood irrigation in tree basins is widely used in citrus orchards, but it has several drawbacks in terms of water losses through conveyance, percolation, evaporation and distribution, yet without much adverse impact on growth, yield, and fruit quality. Fruit yield of ‘Nagpur’ mandarin with different microirrigation systems on Vertic Ustochrept was significantly higher (48.2-58.9 kg/tree) over basin irrigation (32.3 kg/tree) with corresponding WUE of 0.19-0.24 versus 0.109 tonne/ha/cm and leaf N content of 2.38-2.42% versus 2.01-2.12%. Fertigation (application of nutrients through irrigation) produce better results in improving tree growth, fruit yield, quality, reserve pool of soil nutrients, and consequently plant nutritional status. Besides, better mobility of nutrients, fertigation has been shown to have several advantages over broadcast application of granular fertilizer with respect to growth response, nutrient uptake, effective placement of nutrients and flexibility in application, frequency development of uniform root distribution in wetted zone, an important prerequisite for better FUE fruit yield and improvement in fruit quality.